Strategi Pelayanan dalam Meningkatkan Loyalitas Nasabah Ditinjau dari Manajemen Syariah Studi di PT. Asuransi Jiwa Syariah Bumiputera Cabang Kediri - Caspirosi, Loris; Yuliani, Yuliani (Sharia Business Management Study Program, Faculty of Economics and Islamic Business at IAIN Kediri, 2023)
The development of sharia life insurance which is increasingly having an increase makes PT. Bumiputera Sharia Life Insurance Kediri Branch must have excellent service. For that PT. Bumiputera Sharia Life Insurance, Kediri Branch has developed a service strategy to increase customer loyalty. By increasing customer loyalty, it will make it easier for PT. Bumiputera Sharia Life Insurance Kediri Branch to win business competition. The purpose of this study was to determine the service strategy in increasing customer loyalty at PT Asuransi Jiwa Syariah Bumiputera, Kediri Branch, in terms of sharia management. This research uses a qualitative approach with the type of research is a case study. Collecting data using the method of observation, interviews, and documentation. Checking the validity of the data used is the extension of participation, observation persistence, and triangulation. The result of this research is PT. The Bumiputera Sharia Life Insurance, Kediri Branch, provides services using a family approach strategy, where the approach taken is to maintain closeness with customers. When viewed from the five service indicators, namely reliability, responsiveness, assurance, empathy and physical evidence, then the four indicators have been implemented. However, in terms of physical evidence indicators, there are still deficiencies that are not appropriate, namely in the buildings and facilities provided. Implementation of sharia management at PT. Bumiputera Sharia Life Insurance, Kediri Branch, adheres to the principle of justice, namely the family approach. Then for the communicative principle lies in the application of speaking, listening, and looking culture. As for the principles of trust and accountability, namely the transparency of the insurer and all responsibilities for customer funds.